Influenza immunization does not predominantly alter levels of phenytoin, and cytochrome P-450 enzymes in epileptic patients receiving phenytoin monotherapy - Atiwat Soontornpun (2020)
© 2020 Elsevier B.V. Objective: The study aims to test the effect of influenza vaccination on phenytoin, CYP2C9, and IFNγ levels in epileptic patients receiving phenytoin monotherapy Methods: Thirty-one epileptic patients receiving stable-dose phenytoin monotherapy were enrolled onto the study. Serum concentrations of phenytoin, CYP2C9, and IFNγ were compared before and after influenza immunization. The participants were given 0.5 mL of quadrivalent influenza vaccine types A and B subvirion. Blood samples were drawn at baseline, and days 3, 7, 14 post-immunization. The outcomes were levels of phenytoin, CYP2C9, IFNγ, and the incidence of adverse events. Results: No significant changes in serum phenytoin, IFNγ, and CYP2C9 levels between baseline and days 3, 7, and 14 after immunization were found. The mean levels of phenytoin, IFNγ, and CYP2C9, respectively, were 11.94 ± 7.43, 1.14 ± 0.98, and 47.69 ± 37.53 pg/mL (baseline); 12.15 ± 6.57, 2.13 ± 3.41, and 49.44 ± 39.83 pg/mL (day 3); 12.19 ± 7.69, 1.15 ± 0.94, and 49.48 ± 33.83 pg/mL (day 7); 12.79 ± 7.94, 2.15 ± 3.11, and 53.65 ± 40.91 pg/mL (day 14). The incidence of vaccine-related adverse events, which were generally mild and resolved without clinical consequences, was 58.1 %. No seizure or changes in seizure frequency were observed during the study. One patient experienced dizziness and ataxia which were symptoms attributed to phenytoin toxicity (34.57 μg/mL) by day 14. Conclusions: Influenza vaccine has no significant effect on the serum phenytoin and CYP2C9 levels in epileptic patients receiving chronic phenytoin monotherapy. The administration of influenza vaccine to epileptic patients receiving phenytoin monotherapy appears to be safe. Therefore, it is not necessary to routinely measure the serum phenytoin level after influenza immunization.